Spatial richness analysis and an evaluation of extinction risk for the genus Pachyphytum (Crassulaceae), with the description of a new species from Sierra Madre Occidental, Mexico - Castro-Castro, Arturo; Ortiz-Brunel, Juan Pablo; Ávila-González, Heriberto; Lichter-Marck, Isaac H.; Carrillo-Reyes, Pablo; López-Enríquez, Irma Lorena; Barvosa-Jiménez, Marco Antonio (Phytotaxa, 2023)
Pachyphytum is a genus of rupicolous succulents endemic to central Mexico. Here, we present a comprehensive list of currently recognized taxa in Pachyphytum with a review of biogeographical distribution data, a spatial richness analysis, and conservation assessments based on herbarium records and field work. Pachyphytum has been documented in 11 Mexican states, with the highest concentration of species (14) occurring in xerophilous scrubland, Chihuahuan Desert, and the Sierra Madre Oriental. All species of Pachyphytum are narrow endemics and were therefore categorized as at-risk of extinction according to IUCN criteria. Currently, taxa in Pachyphytum do not have formal protected status due to lack of inclusion on Mexico’s list of endangered species. During fieldwork in preparation for this research, an undescribed Pachyphytum was encountered in Durango state, which we here describe as a new species based on a detailed morphological comparative study.